2017
DOI: 10.1111/oik.04190
|View full text |Cite
|
Sign up to set email alerts
|

Trophic and non‐trophic interactions influence the mechanisms underlying biodiversity–ecosystem functioning relationships under different abiotic conditions

Abstract: Plant diversity effects on ecosystem functioning usually have been studied from a plant perspective. However, the mechanisms underlying biodiversity–ecosystem functioning relationships may also depend on positive or negative interactions between plants and other biotic and abiotic factors, which remain poorly understood. Here we assessed whether plant–herbivore and/or plant–detritivore interactions modify the biodiversity–ecosystem functioning relationship and the mechanisms underlying biodiversity effects, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Our results showed that the mycorrhiza colonization frequency of roots can mediate root biomass production, while this may also diminish under drought stress. This result further exemplifies how biotic interactions and biodiversity-ecosystem function relationships depend on environmental conditions 161 . Trait-based approaches with a temporal dimension are necessary to mechanistically understand identity effects, mycorrhizal functions and their temporal aspects 33,61,127 .…”
Section: Discussionmentioning
confidence: 57%
“…Our results showed that the mycorrhiza colonization frequency of roots can mediate root biomass production, while this may also diminish under drought stress. This result further exemplifies how biotic interactions and biodiversity-ecosystem function relationships depend on environmental conditions 161 . Trait-based approaches with a temporal dimension are necessary to mechanistically understand identity effects, mycorrhizal functions and their temporal aspects 33,61,127 .…”
Section: Discussionmentioning
confidence: 57%
“…Alternatively, diverse communities may have higher functioning because of an elevated probability of containing and becoming dominated by one or a few productive species (Loreau and Hector, 2001). Moreover, there is growing evidence that biotic interactions across trophic levels are important drivers of biodiversity effects (Maron et al, 2011; Schnitzer et al, 2011; Eisenhauer et al, 2012a) and that these interactions are significantly modulated by environmental conditions (Guerrero-Ramírez and Eisenhauer, 2017). As a consequence, biodiversity effects may depend on the environmental context, such as climatic conditions and resource availability (Craven et al, 2016; Guerrero-Ramírez et al, 2017), and thus may change in future environments.…”
Section: Introductionmentioning
confidence: 99%
“…Diversity effects arise from interactions among individuals and between individuals and their environments (Craven et al, 2016; Guerrero‐Ramirez & Eisenhauer, 2017). Because, environmental change—including disturbance—can modify the strength and direction of species interactions as well as how individuals’ response to a disturbance, diversity effects can vary across environmental conditions (Cardinale et al, 2000; Fridley, 2002; Steudel et al, 2012; Worm et al, 2002).…”
Section: Discussionmentioning
confidence: 99%